Peran Lingkungan Pembelajaran terhadap Kualitas Proses Belajar Mengajar Kelas V di Sekolah Dasar - Rahmilawati Ritonga; Salsabilla Cahaya Putri; Arin Huwaida; Nengsi Amelia Nainggolan; Chade Chatena Munte; Syahroini Syahroini (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The learning environment plays a strategic role in determining the quality of the teaching and learning process, particularly for fifth-grade elementary school students who are at a crucial stage of cognitive and social development. This study aims to analyze the influence of the learning environment on the effectiveness of learning in Grade V of elementary school using a descriptive qualitative approach through literature review. The learning environment examined includes physical aspects (such as facilities, classroom layout, and lighting) as well as non-physical aspects (such as social interaction, emotional atmosphere, and teacher support). The findings reveal that a conducive learning environment significantly enhances students’ motivation, engagement, and academic achievement. These results are supported by Piaget’s and Vygotsky’s constructivist theories, as well as Bandura’s social learning theory, which emphasize the importance of interaction between learners and their environment in constructing knowledge and skills. The study recommends strong collaboration among schools, teachers, and education stakeholders to create a holistic, safe, and supportive learning environment that fosters students’ academic and personal development.